Predicting of tool wear on machining parameters using design of experiment (DOE) methodology - Faizal Zamri, Zainal Abidin (2007)
Lately, there are many factories in Malaysia were build and increasing along with the development of the economic structure and national rapid development. However, not all the engineers in those factories are using proper statistical analysis in their research in the industry. Throughout this project which "Predicting of Tool Wear on Machining Parameters Using Design of Experiment (DOE) Methodology", the result will be analyzed using DOE methodology and software. Implementing DOE method, the experiment is based on 2 Full Factorial Experiment. The study is focusing on turning process which one of cutting process. The experiment is conducted using lathe machine and measured by using image analyzer. The analysis consists of four main elements which are finding the significant factor, relationship between parameters, Analysis of Variance (ANOVA) and estimated result at optimum condition. Finally, the outcome of the study is to determine if the DOE methodology may predict of tool wear and its effectiveness for statistical analysis.